Deskripsi Kendala Guru dalam Penerapan Kurikulum Merdeka di Sekolah Dasar Negeri 74 Pontianak Barat - Nurdini Maulida; Dyoty Auliya Vilda Ghasya; Rio Pranata (Journal on Education, 2023)
The demands of changing times encourage changes in various fields including the field of Education, Education policies in order to improve the quality and quality of Education in Indonesia by improving and updating the curriculum used. The change in the 2013 curriculum to an independent curriculum has had an impact on various components of education including teachers in the implementation of an independent curriculum facing several obstacles. The purpose of this study was to describe the teacher's constraints in implementing the independent curriculum at SDN 74 West Pontianak. This type of research uses qualitative research with descriptive methods. The results of the study showed that in implementing the independent curriculum at SDN 74 West Pontianak the teacher experienced obstacles: lack of training related to the independent curriculum, limited learning facilities and infrastructure, limited learning resources for students' textbooks.